Posterior inserting of the upper fascicle of the lateral pterygoid muscle in anatomical preparations - Sotomayor Camayo, Justiniano (2013)
This study aimed to determine the prevalence of posterior insertion of the superior fasciculus of the external pterygoid muscle (Lateral Pteridoideo) in anatomical preparations of adult corpses. 4 dead between 25 and 60 years was selected, was dissected up to the zygomatic fossa to expose the lateral pterygoid muscle and the components of the ATM. Subsequent insertion ratio upper lateral pterygoid muscle bundle with respect to the disc joint, joint capsule and condylar identified, being said insert was articular disk. Macroscopically, the upper bundle insertion lateral pterygoid muscle at condyle neck was observed.